Association between previous infection with SARS CoV-2 and the risk of self-reported symptoms after mRNA BNT162b2 vaccination: Data from 3, 078 health care workers. (June 2021) - d'Arminio Monforte, Antonella; Tavelli, Alessandro; Perrone, Pier Mario; Za, Alessandro; Razzini, Katia; Tomasoni, Daniele; Bordoni, Vittorio; Romanò, Luisa; Orfeo, Nicola; Marchetti, Giulia; Colosio, Claudio
Abstract: Background: Health care workers (HCWs) are at high risk of contracting an infection by SARS CoV-2 and thus they are a priority for vaccination. We hereby aim to investigate whether the risk of severe and moderate systemic symptoms (MSS) after vaccination is higher in HCWs with a history of previous COVID-19. Methods: An online questionnaire was offered to the cohort all HCWs undergoing anti-SARS CoV-2 mRNA BNT162b2 vaccination between January 4th and February 9th 2021 in two large tertiary hospitals (ASST Santi Paolo and Carlo) in Milan, Italy. Previous SARS-CoV-2 infection/COVID-19 was recorded. Local and systemic symptoms after each of the two doses were reported. MSS were those either interfering with daily activities or resulting in time off-work. Factors associated to MSS were identified by logistic regression. Findings: 3, 078 HCW were included. Previous SARS-CoV-2 infection/COVID-19 occurred in 396 subjects (12·9%). 59·6% suffered from ≥ 1 local or systemic symptom after the first and 73·4% after the second dose. MSS occurred in 6·3% of cases (14·4% with previous vs 5·1% with no COVID-19 p <0·001) and in 28·3% (24·5% in COVID-19 vs 28·3% no COVID, p = 0·074) after the first and second dose, respectively. Subjects already experiencing COVID-19 had an independent 3-fold higher risk of MSS after the first and a 30% lower risk after the second dose. No severe adverse events were reported. Interpretation: Our data confirm in a real-world setting, the lack of severe adverse events and the short duration of reactogenicity in already infected HCWs. Possible differences in immune reactivity are drivers of MSS among this group of HCWs, as well as among females and younger individuals. Funding: None.